Penerapan Pendekatan Komunikatif Dalam Meningkatkan Kemampuan Berpidato Pada Mahasiswa - gusnayetti, dra.gusnayetti (LPPM STISIP IMAM BONJOL, 2024)
The objectives to be achieved in this study are to determine students' speech abilities in learning Indonesian through the application of a communicative approach and student learning outcomes in speeches through the application of a communicative approach. There are still many students who cannot place words according to the structure of language rules, unpreparedness in delivering speeches, unclear pronunciation in delivering speeches, poor speech content, volume that is not loud, body position and eye contact that are not good and pauses not appropriate in delivering a speech and when giving a speech in front of the classroom students feel insecure, causing fear, nervousness, halting speech, and unclear articulation. This is because the procedures used still use theoretical learning, and it is also caused by the learning process which still uses the lecture method and does not use a communicative approach through training and practicum methods in the application of learning Indonesian speech subjects, so that many students feel bored with these conditions and resulted in students obtaining unsatisfactory learning outcomes